Foreign direct investment and economic growth in Malaysia: the role of financial development - Ismail, Nik Zirwatul Fatihah; Wan Ngah, Wan Azman Saini (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This study investigates the effectiveness of financial development in mediating the impact of foreign direct investment (FDI) on economic growth in Malaysia during the period of 1975 to 2009. The empirical results, based on the autoregressive distributed lag (ARDL) method shows that there is a long run relationship between FDI, investment of GDP, total labor, human capital, financial development and interaction term (FDI and financial development) with GDP growth. Besides, the entire variable has direct impact on economic growth except total labor and human capital which is has no direct impact on economic growth. Furthermore, the result shows that the important role played by financial development in mediating the FDI-effect occur both in the short and long run.